Defining the Cellular Basis for Poor Muscle Performance in Diabetic Peripheral Neuropathy - Kathryn L. Bohnert MS (Foot & Ankle Orthopaedics, 2019)
Category: Diabetes Introduction/Purpose: Type 2 Diabetes Mellitus (T2DM) is a major contributor to physical disability. For individuals with T2DM that develop diabetic peripheral neuropathy (DPN), progression to disability is accelerated, driven by declines in lower extremity strength, altered gait, foot deformity and amputation. Pathology of foot and calf muscles is thought to drive early strength losses, making muscle an attractive therapeutic target. However, a lack of cell-level data has held back targeted interventions as the underlying processes remain poorly defined. In this work, we characterize diabetic muscle pathology at the cell and gene level using samples obtained during surgery from individuals with and without DPN. We hypothesize that DPN muscle has a predominately degenerative, rather than atrophic, pathology requiring regenerative approaches in addition to standard strengthening paradigms. Methods: 11 participants undergoing below-the-knee amputation have been enrolled in this study - 6 with DPN and 5 without diabetes or neuropathy. During the surgery, biopsies were acquired from the medial gastrocnemius (MG) and abductor hallucis (AH) muscles to compare the less affected proximal MG to the more affected distal AH. Muscle was separated from intramuscular adipose tissue (IMAT) and connective tissue under a dissecting microscope and flash frozen for histological sectioning and gene expression analysis. 10um sections of fresh frozen muscle were stained with hematoxylin & eosin (H&E) to assess gross morphology, Pax7 to assess muscle progenitor (satellite) cells and PDGFRa to assess fibro/adipogenic progenitor cells. Gene expression was assessed by genechip analysis. Quantitative data were normalized within subjects (AH/MG) and compared between groups by t-test. Results: H&E staining revealed extensive pathology in DPN samples. Extremely small diameter muscle fibers (asterisks, Fig 1A) were found on the border of fascicles and in separate fascicular regions. Large areas were comprised only of connective tissue and IMAT, especially in the severely affected AH muscles (Fig 1A, lower right). Degenerating and regenerated fibers could be identified by remnant cytoplasm in the basal lamina with cellular infiltrate and centralized nuclei (arrows, Fig 1A), respectively. These features were absent in control muscle. In the DPN samples, gene expression data showed little to no change in atrophic pathways (atrogenes, ubiquitin ligases, calpains/caspases), but substantial upregulation of regenerative pathways (myogenesis, injury response, neuromuscular generation) in the more affected AH (Fig 1B). Conclusion: We demonstrate that DPN muscle pathology is characterized by extensive degeneration with fibro/fatty tissue replacement. Fiber degeneration is likely driven by impaired innervation. The muscle appears to attempt to compensate for this by regenerating fibers, but is progressively unsuccessful as connective tissue and fat are laid down in place of new fibers. Thus, therapeutic strategies that aid in regeneration may improve rehabilitative efforts to improve muscle strength with DPN.